Neurodevelopment Outcome among Preterm Infants Admitted in Neonatal Intensive Care Unit (Journal of Dhaka Medical College, 2024)
Introduction: With increasing the survival rates of premature babies, the management of long term complications, especially neurodevelopmental disorder is becoming an important issue for a better life.Aims: To assess the factors associated with adverse neurodevelopment outcome among preterminfants admitted in Neonatal Intensive Care Unit (NICU).Methods and Material: This prospective cohort study was conducted in Department of Neonatology, BSMMU, Dhaka, Bangladesh. Premature infants (